Frequency of Post-Operative Wound Infection Following Intestinal Stoma Closure: A Cross-Sectional Study (Review Journal of Neurological & Medical Sciences Review, 2025)
Objective: The aim of this study is to find out the rate of post-operative wound infection in intestinal stoma closure cases, and to identify risk factors for the infection. Design: A cross-sectional study is carried out to determine the incidence of POWI among patients who undergo intestinal stoma closure. Setting: The study was conducted in the General Surgery Department, Lady Reading Hospital, Peshawar. Subjects: A total of 116 patients who had been stoma closure on intestine were involved in this study. Interventions: Surgical intervention involved the use of typical operational protocol in relation to the use of prophylactic antibiotics, the closure of intestinal stoma, and the standard post-operative wound cares practices. Main Outcome Measures: Post-operative wound infection was characterized by such clinical manifestation as fever, pain, erythema, cellulitis, and purulent discharge subsequent to the operation within 10 days. Results: It was established that 13.8% of the patients were found to have a post-operative wound infection after intestinal stoma closure. Older age and the occurrence of diabetes were the most important factors associated with increased risk of wound infection, whereas no significant association was established with the patient’s gender or hypertension. Fever and pain were the most prevalent clinical features of infection, with a high prevalence rate of pus discharge. Conclusions: Post-operative infection of the wound in intestinal stoma closures is associated with age and diabetes, according to the results. Being attentive to symptoms, like fever and purulent discharge, and specific preventive interventions could prevent infections. This article shows the importance of making post-surgery care for high-risk patients to increase the benefits of the surgery and patient wellness they have undergone.Keywords: Intestinal Stoma Closure, Post-Operative Wound Infection, Surgical Site Infection, Purulent discharge, Diabetes, Surgical infection, Wound Healing, Perioperative Care, Prophylactic antibiotics, post-operative care, General surgery.